Kekerasan dalam Rumah Tangga (KDRT) Dampak Sosiologis Anak Tinjauan Maqasid Syar’iyah - Chaliddin, Chaliddin; Nazaruddin, Nazaruddin (Syarah: Jurnal Hukum Islam dan Ekonomi, 2022)
Household as a place of violence often is a phenomenon of a life of its inhabitants consisting of various statuses, such as husband and wife, parents, children, people who have blood relations, people who work to help the household life, others who live, and people who still or have lived together in a household. The intensity of domestic violence in Indonesia in general and Aceh is particularly significant which leads to the sociological impact of children in their growth and development in terms of maqasidul Syariyah. Problem formulation 1. How is the cause of domestic violence (KDRT)? 2. How is the sociological impact of children due to domestic violence (KDRT) and maqasid syar'iyah perspective? 3.What are the steps taken to minimize the occurrence of domestic violence (KDRT)? Writing methodology which writer use in this research is library research which is descriptive analysis, The result of this writing are: 1. Cause of violence because of lack of education, existence of unequal power relationship between husband and wife. 2. Impact on the wife feeling depressed, shock, trauma, fear, anger, high emotion and explosive, couples, and depression, the impact of children make it has a tendency as nervous, easy to worry when faced with problems, often wetting, restless and uneasy, poor performance at school. 3. Lankah to minimize socialization to the community about domestic violence is an act that can not be justified, the role of mass media. Print media, television, cinema, radio and internet are very influential to prevent and reduce domestic violence.